2021
DOI: 10.1136/bmjgh-2021-005798
|View full text |Cite
|
Sign up to set email alerts
|

Trends and outcomes in primary health care expenditures in low-income and middle-income countries, 2000–2017

Abstract: IntroductionAs the world responds to COVID-19 and aims for the Sustainable Development Goals, the potential for primary healthcare (PHC) is substantial, although the trends and effectiveness of PHC expenditure are unknown. We estimate PHC expenditure for each low-income and middle-income country between 2000 and 2017 and test which health outputs and outcomes were associated with PHC expenditure.MethodsWe used three data sources to estimate PHC expenditures: recently published health expenditure estimates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…When compared to the multi-country analyses of PHC per capita costs that feature Ethiopia, this study’s actual per capita cost estimates tend to be lower. The Institute for Health Metrics and Evaluation (IHME) Global Burden of Disease (GBD) estimated Ethiopia’s PHC expenditure per capita to be US$ 17.20 in 2017 ( 28 ), while the World Health Organization (WHO) reported it to be US$ 21.12 in 2019 ( 29 ). There are considerable methodological differences between these studies and our work and both IHME GBD and WHO estimates rely on country-reported health expenditure data that includes private providers and above service level expenditures, which this study does not consider.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the multi-country analyses of PHC per capita costs that feature Ethiopia, this study’s actual per capita cost estimates tend to be lower. The Institute for Health Metrics and Evaluation (IHME) Global Burden of Disease (GBD) estimated Ethiopia’s PHC expenditure per capita to be US$ 17.20 in 2017 ( 28 ), while the World Health Organization (WHO) reported it to be US$ 21.12 in 2019 ( 29 ). There are considerable methodological differences between these studies and our work and both IHME GBD and WHO estimates rely on country-reported health expenditure data that includes private providers and above service level expenditures, which this study does not consider.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing state-level estimates with national figures for Nigeria is challenging since national data likely conceal substantial state-level variation. Per capita PHC cost estimates for Nigeria estimated by the Institute for Health Metrics and Evaluation (IHME) and the World Health Organization (WHO) ranged from US$ 31 in 2017 ( 43 ) to US$ 40 in 2020 ( 11 ). Although most of our estimates for Kaduna and Kano are lower, the IHME and WHO base their calculations on country-reported health expenditures that include components not considered in our study, including above service-level overheads and spending at private providers ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent efforts by Randhawa4 and Veillard et al 5 have demonstrated the relationship between inputs and outcomes of the PHC system. Previous studies also highlighted that PHC capacity, including the availability of providers, governance and financing, has been found to impact PHC-related outcomes in LMICs at the national level 6–10. In addition, several studies have identified relationships between elements of high-quality PHC and performance at the national level 2 11–14.…”
Section: Introductionmentioning
confidence: 99%